2007
DOI: 10.1089/neu.2005.356e
|View full text |Cite
|
Sign up to set email alerts
|

Effective ICP Reduction by Decompressive Craniectomy in Patients with Severe Traumatic Brain Injury Treated by an ICP-Targeted Therapy

Abstract: Severe traumatic brain injury (TBI) is one of the major causes of death in younger age groups. In Umeå, Sweden, an intracranial pressure (ICP) targeted therapy protocol, the Lund concept, has been used in treatment of severe TBI since 1994. Decompressive craniectomy is used as a protocolguided treatment step. The primary aim of the investigation was to study the effect of craniectomy on ICP changes over time in patients with severe TBI treated by an ICP-targeted protocol. In this retrospective study, all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
1
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(140 citation statements)
references
References 25 publications
7
118
1
8
Order By: Relevance
“…2,87 As a rescue therapy, decompressive craniectomy has been shown to reliably abort progressive increases in ICP. 59,89 Decompressive craniectomy also brings about changes in CBF and CSF dynamics. 7,20,24,96,97 Cine MR imaging studies have demonstrated impaired CSF flow across the craniovertebral junction at the skull base, which improves following cranioplasty repair of the skull defect.…”
Section: Department Of Neurosurgical Surgery School Of Medicine; Andmentioning
confidence: 99%
See 2 more Smart Citations
“…2,87 As a rescue therapy, decompressive craniectomy has been shown to reliably abort progressive increases in ICP. 59,89 Decompressive craniectomy also brings about changes in CBF and CSF dynamics. 7,20,24,96,97 Cine MR imaging studies have demonstrated impaired CSF flow across the craniovertebral junction at the skull base, which improves following cranioplasty repair of the skull defect.…”
Section: Department Of Neurosurgical Surgery School Of Medicine; Andmentioning
confidence: 99%
“…96 In addition, loss of resistance in brain tissue lacking a protective skull invokes a higher hydrostatic pressure gradient that may permit transcapillary leakage of edema fluid. 59 Brain edema following decompressive craniectomy has been modeled in animal studies of injury using Evans blue dye extravasation. 15,25,69 Cooper et al 15 found a 7-fold increase in edema formation as determined by Evans blue dye extravasation following craniectomy.…”
Section: Perioperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of refractory ICP has been shown to be a major predictor of mortality following TBI, 21,25,31,42 and many studies have confirmed the positive effects of craniectomy on reducing ICP following TBI. 1,37,49,50 However, few randomized controlled studies exist that specifically address the effectiveness of craniectomy in pediatric populations to improve clinical outcome. In most current adult and pediatric studies, refractory ICP hypertension is often defined as ICP > 20 mm Hg for some defined time period.…”
Section: Surgical Interventions For Tbi In the Pediatric Populationmentioning
confidence: 99%
“…Decompressive craniectomy (DC) has been accepted as a therapeutic strategy for patients with medically refractory increased intracranial pressure (ICP) secondary to severe traumatic brain injury (TBI), malignant middle cerebral artery (MCA) or internal cerebral artery (ICA) infarction, large hypertensive intracerebral hemorrhage (ICH), high-grade aneurysmal subarachnoid hemorrhage and severe cerebral venous sinus thrombosis (5,7,12,13,14,17,20).…”
Section: Introductionmentioning
confidence: 99%